НКО в современной России: анализ участия в политических протестах - Всеволод Бедерсон; Вячеслав Логинов (ЖУРНАЛ СОЦИОЛОГИИ И СОЦИАЛЬНОЙ АНТРОПОЛОГИИ, 2020)
Our analysis focuses on the question why professional NGOs in contemporary Russia, in addition to conventional non-political forms of interaction with the authorities, practice political protests. The article is based on data on protests in the Russian regions in 2013 and in 2015. We examine political and organizational factors that facilitate and hinder participation of NGOs in protests with political demands. We use logistic binomial regression method to analyze how the participation of NGOs in protests is related to political requirements and the membership of NGOs in advisory bodies, in the All-Russian Popular Front, participation in elections, the age / experience of NGOs, and the field of activity of NGOs. The results of our analysis are contradictory. On the one hand, none of the predictors has statistical visibility at the least conventional level. On the other hand, the direction of the association of the variables corresponds to the theoretical expectation and hypotheses. Membership in advisory bodies, in ARPF and participation in elections is negatively related to the participation of NGOs in protests with political demands. An older age, contrary to expectations, has a positive relationship. The field of activity of NGOs in all selected categories does not show statistical visibility.